The British Growth Crisis
XII, 323 p.
Keywords: Britain remains mired in the most severe and prolonged economic crisis that it has faced since the 1930s. What would it take to find a new, more stable and more sustainable growth model for Britain in the years ahead? This important volume written by a number of influential commentators seeks to provide some answers.